2017
DOI: 10.21037/jgo.2017.08.08
|View full text |Cite
|
Sign up to set email alerts
|

Management of liver metastases from gastrointestinal stromal tumors: where do we stand?

Abstract: Abstract:The recommended management of liver metastases (LM) from gastrointestinal stromal tumors (GISTs) disease consists of perioperative administration of tyrosine kinase inhibitors (TKIs) and surgical resection. The aim of our study was to investigate the efficacy of this therapeutic approach. Studies reporting outcomes for patients underwent liver resection from metastatic gastrointestinal stromal tumor (GIST) were overviewed. Eleven studies were included, which enrolled 240 patients with liver metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 29 publications
0
23
0
2
Order By: Relevance
“…For GIST, it has been reported that 15% of patients are primarily resistant to the drug[ 46 ], In general, 88% of patients suffer from recurrence about 2 years after imatinib treatment due to the secondary resistance mutations in additional KIT exons[ 47 , 48 ]. Given the poor results of palliative treatment including chemotherapy, ablation, and TACE in patients with tyrosine kinase inhibitor drug resistance, liver transplantation may be the only treatment that may improve prognosis and prolong the overall survival time[ 49 ]. In a case reported by Joyon et al[ 23 ], a patient received a first course of lipiodol chemoembolization, but a second intrahepatic lesion was discovered in the left lobe 3 mo later.…”
Section: Phgist Treatmentmentioning
confidence: 99%
“…For GIST, it has been reported that 15% of patients are primarily resistant to the drug[ 46 ], In general, 88% of patients suffer from recurrence about 2 years after imatinib treatment due to the secondary resistance mutations in additional KIT exons[ 47 , 48 ]. Given the poor results of palliative treatment including chemotherapy, ablation, and TACE in patients with tyrosine kinase inhibitor drug resistance, liver transplantation may be the only treatment that may improve prognosis and prolong the overall survival time[ 49 ]. In a case reported by Joyon et al[ 23 ], a patient received a first course of lipiodol chemoembolization, but a second intrahepatic lesion was discovered in the left lobe 3 mo later.…”
Section: Phgist Treatmentmentioning
confidence: 99%
“…[32][33][34]38 As stated, the optimal timing of metastasectomy remains controversial, but is recommended to take place within 3 to 6 months of TKI initiation to balance the time to optimal response with the chance of acquiring resistance. 7,34,39 Typically imatinib is stopped just a few days prior to resection and restarted as soon as the patient has recovered from surgery with adequate wound healing and normalizing liver function tests (ideally within 3-4 postoperative weeks). The use of adjuvant TKI therapy after resection of GIST LM is a matter of debate, but generally is considered standard practice, even after a curative-intent operation.…”
Section: Traditional Management Of Metastatic Gist To the Livermentioning
confidence: 99%
“…Reports of median survivals ranging from 33 to 60 months and 5-year OS rates as high as 91% have been achieved. 34,39,43 Importantly, postoperative morbidity and mortality remain low. 39 Complication rates in recent series range from 0 to 33%.…”
Section: Outcomes After Liver Resection For Gist Lmmentioning
confidence: 99%
See 2 more Smart Citations